Biotin-Labelled Clavulanic Acid to Identify Proteins Target for Haptenation in Serum: Implications in Allergy Studies - Martín-Serrano, Ángela; Gonzalez-Morena, Juan M.; Barbero, Nekane; Ariza, Adriana; Sánchez Gómez, Francisco J.; Pérez-Inestrosa, Ezequiel; Pérez-Sala, Dolores; Torres, Maria J.; Montañez, María I. (Frontiers in Pharmacology, 2020)
Clavulanic acid (CLV) and amoxicillin, frequently administered in combination, can be independently involved in allergic reactions. Protein haptenation with β-lactams is considered necessary to activate the immune system. The aim of this study was to assess the suitability of biotinylated analogues of CLV as probes to study protein haptenation by this β-lactam. Two synthetic approaches afforded the labelling of CLV through esterification of its carboxylic group with a biotin moiety, via either direct binding (CLV-B) or tetraethylenglycol linker (CLV-TEG-B). The second analogue offered advantages as solubility in aqueous solution and potential lower steric hindrance for both intended interactions, with the protein and with avidin. NMR reactivity studies showed that both CLV and CLV-TEG-B reacts through β-lactam ring opening by aliphatic amino nitrogen, however with different stability of resulting conjugates. Unlike CLV conjugates, that promoted the decomposition of clavulanate fragment, the conjugates obtained with the CLV-TEG-B remained linked, as a whole structure including biotin, to nucleophile and showed a better stability. This was a desired key feature to allow CLV-TEG-B conjugated protein detection at great sensitivity. We have used biotin detection and mass spectrometry (MS) to detect the haptenation of human serum albumin (HSA) and human serum proteins. MS of conjugates showed that HSA could be modified by CLV-TEG-B. Remarkably, HSA preincubation with CLV excess only reduced moderately the incorporation of CLV-TEG-B, which could be attributed to different protein interferences. The CLV-TEG-B fragment with opened β-lactam was detected bound to the 404-430HSA peptide of the treated protein. Incubation of human serum with CLV-TEG-B resulted in the haptenation of several proteins that were identified by 2D-electrophoresis and peptide mass fingerprinting as HSA, haptoglobin, and heavy and light chains of immunoglobulins. Taken together, our results show that tagged-CLV keeps some of the CLV features. Moreover, although we observe a different behaviour in the conjugate stability and in the site of protein modification, the similar reactivity indicates that it could constitute a valuable tool to identify protein targets for haptenation by CLV with high sensitivity to get insights into the activation of the immune system by CLV and mechanisms involved in β-lactams allergy.